FTMOntology: An Ontology to Fill the Semantic Gap between Music, Mood, Personality, and Human Physiology - Marques, Caio Miguel; Von Zuben, Joao; Guilherme, Ivan Rizzo [UNESP]; Meersman, R.; Dillion, T.; Herrero, P. (Springer, 2011)
This paper presents a domain ontology, the FeelingTheMusic Ontology - FTMOntology. FTMOntology is designed to represent the complex domain of music and how it relates to other domains like mood, personality and physiology. This includes representing the main concepts and relations of music domain with each of the above-mentioned domains. The concepts and relations between music, mood, personality and physiology. The main contribution of this work is to model and relate these different domains in a consistent ontology.
Keywords: Ontology; music semantic model; semantic retrieval